Shadow Economy in the Context of Economic Crisis - Strnad, Vladimír; Chytilová, Helena; Čermáková, Klára; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2014)
This thesis examines development of the shadow economy in context of crisis on sample of 46 countries, divided into two groups, high income OECD countries and transition countries. In order to examine the effect of crisis on the shadow economy, we compare two panel analyses, first ranging over period 2005-2007 and second 2008-2010. We found that the effect of driving forces behind the shadow economy differs in those two panels, suggesting that crisis has had a significant effect on the development of the shadow economy. The results suggest that GDP growth has positive effect on the size of the shadow economy after the crisis.
Vedoucí práce: Helena Chytilová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses